2018
DOI: 10.1111/cen.13812
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic accuracy of parathyroid hormone levels in washout samples of suspicious parathyroid adenomas: A single‐centre retrospective cohort study

Abstract: According to the literature, PTH determination in washout samples has a specificity of 75%-100% and sensitivity of 70%-100%. This approach has better results than both cytology and scintigraphy in case of concomitant multinodular thyroid disease in experienced hands. Although there is not a definite cut-off for PTH levels in washout samples, we agree with the need of ratios rather than cut-offs in this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The characteristics of the included articles are summarized in Table 1 (19,20,21,22,23,24,25,26,27). The papers were published between 1998 and 2018, had sample sizes ranging from 6 to 44 patients.…”
Section: Qualitative Analysis (Systematic Review)mentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the included articles are summarized in Table 1 (19,20,21,22,23,24,25,26,27). The papers were published between 1998 and 2018, had sample sizes ranging from 6 to 44 patients.…”
Section: Qualitative Analysis (Systematic Review)mentioning
confidence: 99%
“…FNA-PTH was performed with a 21-to 27-gauge needle, washed out with 0.5-1 mL of 0.9% saline or PTH-free serum. The result was considered as positive if higher than patient's serum PTH level at the time of sampling in four studies (19,21,24,25), two times this level in one (22); the remaining papers reported a cutoff ranging from 40 to 103 pg/mL (Table 2) (20,23,26,27). Overall, 222 lesions in 182 patients were evaluated.…”
Section: Qualitative Analysis (Systematic Review)mentioning
confidence: 99%
“…found that the PTH washout/plasma PTH ratio over 3.05 had a specificity of 89% [17]. This data suggests that when higher PTH washout / plasma PTH ratio is accepted as positive cut-off value, it may increase false negative results.…”
Section: Discussionmentioning
confidence: 86%
“…There are studies suggesting different positive cut-off values for PTH washout. Gokcay et al found sensitivity at 90.3% and specificity at 88.9% in determining parathyroid lesion when they received 436.5 pg/mL as the positive cut-off value for PTH washout [17]. Kiblud et al showed that a PTH washout result of more than 1 000 pg/mL had sensitivity of 75% and PPV of 74% in the verification of parathyroid tissue [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the recently published article of Gökçay Canpolat et al, “Diagnostic accuracy of parathyroid hormone levels in washout samples of suspicious parathyroid adenomas: A single‐centre retrospective cohort study …”
mentioning
confidence: 99%